2021
DOI: 10.1111/raq.12551
|View full text |Cite
|
Sign up to set email alerts
|

The expanding repertoire of immune‐related molecules with antimicrobial activity in penaeid shrimps: a review

Abstract: Shrimps live in a complex aquatic ecosystem with numerous other biotic and abiotic factors, especially pathogenic microorganisms, which require the adaptation of prudent protective and survival strategies. As invertebrates, shrimps reply on humoral and cellular innate immune response mechanisms for protection against pathogens. One integral part of the humoral innate immune defence mechanism involves many biomolecules that are constitutively expressed or induced by pathogens. Shrimps, therefore, produce variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 305 publications
(516 reference statements)
0
12
0
1
Order By: Relevance
“…Hemocyanin, the respiratory copper-containing glycoprotein in mollusks and arthropods, has been implicated in numerous immune-related functions (see recent reviews by ( Aweya et al., 2021 ; Coates and Costa-Paiva, 2020 )). As an important immune response protein, hemocyanin is induced by immune challenge ( Zhao et al., 2016 ; Zheng et al., 2018 ) and undergoes proteolytic degradation to generate peptides with antimicrobial activity ( Destoumieux-Garzon et al., 2001 ; Wen et al., 2016 ; Zhan et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemocyanin, the respiratory copper-containing glycoprotein in mollusks and arthropods, has been implicated in numerous immune-related functions (see recent reviews by ( Aweya et al., 2021 ; Coates and Costa-Paiva, 2020 )). As an important immune response protein, hemocyanin is induced by immune challenge ( Zhao et al., 2016 ; Zheng et al., 2018 ) and undergoes proteolytic degradation to generate peptides with antimicrobial activity ( Destoumieux-Garzon et al., 2001 ; Wen et al., 2016 ; Zhan et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that innate immunity has limited or no memory ( Gourbal et al., 2018 ), the innate immune defense mechanisms have had to evolve or coopt many factors to expand its scale or protection and response repertoire against pathogens and potential pathogens ( Gourbal et al., 2018 ; Netea et al., 2019 ). Thus, most invertebrates encode immune-related proteins ( Aweya et al., 2021 ), including immunoglobulin-like molecules, that enable them mount direct or indirect immune responses by interacting with other proteins/factors via coordinated immune pathways ( Halaby and Mornon, 1998 ). For instance, the fibrinogen-related protein (FREPs) that comprises a C-terminal fibrinogen (FBG) domain and upstream immunoglobulin domains ( Adema, 2015 ) plays important innate immune functions in bay scallop Argopecten irradians ( Zhang et al., 2009a ), mosquito Anopheles gambiae ( Dong and Dimopoulos, 2009 ), and sea cucumber Apostichopus japonicus ( Jiang et al., 2018 ) due to the presence of an NF-κB binding motif on FREP promoter region, which can be activated by pathogens ( Jiang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hemocyanin (HMC) is a large copper-containing respiratory protein found in the hemolymph of mollusks and arthropods. Recently, research revealed that HMC may be a novel and important non-specific innate immune defense molecule ( 2 , 3 ). In crustaceans, HMC is thought to be composed of three distinct classes (α-type, β-type, or γ-type), although a single subunit is able to aggregate into hexameric structures ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the immune significance of HMC was dismissed until the late 1990s when Decker and Rimke demonstrated unequivocally its phenoloxidase activity (1). Further research revealed that HMC may be a novel and important non-specific innate immune defense molecule (2,3). It has been reported that HMC could be functionally converted into phenoloxidase (4) antimicrobial peptides (5)(6)(7)(8), antiviral (9)(10)(11)(12), antitumor agent (13)(14)(15)(16)(17), antifungal (18), agglutinin (19,20), hemolysin (21), and regulatory proteins (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having antimicrobial activity, PAMPs play a significant role in regulating plant growth and development and can be used as food additives [23]. PAMPs have a wide spectrum of antiviral, antifungal, antioxidative, antibacterial, chitinase, and proteinaseinhibitory activities [27] to create physical barriers against the spread and penetration of pathogens using waxy cuticle layers and trichomes, or using chemical barriers to inhibit the growth of the pathogens using a complex cell recognition system and photo hormone networks transcriptional pathways, secondary metabolites, and many diverse proteins [23]. PAMPs also act as prominent chemical barriers in plants to resist abiotic stresses [28].…”
Section: Structure-activity Relationship Of Pampsmentioning
confidence: 99%